The Siskel and Ebert of Financial Markets?: Two Thumbs Down for the Credit Rating Agencies - Frank Partnoy (Washington University Law Quarterly, 1999)
Is a AAA rating of an institution’s bonds any different from a five-star Morningstar rating of a mutual fund, or a four-diamond American Automobile Association rating of a hotel, or a three-star Michelin rating of a restaurant, or a “two-thumbs-up” Siskel and Ebert rating of a film, or a single UL symbol on a blender? And if bond ratings differ from ratings of mutual funds, hotels, restaurants, films, and appliances, to what extent have legal rules caused those differences? To what extent should legal rules operate to minimize differences? This Article addresses these questions.
Keywords: Bonds (Finance); Rating agencies (Finance); Credit ratings; Financial markets